Factors Influencing the Participation of Couples of Reproductive Age in the Family Planning Program in East Sumalata District, North Gorontalo Regency - Miftakhul Huda; Yakup Yakup; Mohamad Afan Suyanto; Olfin Ishak; Elfis Mus Abdul (LPPPIPublishing, 2026)
This study examines the factors influencing the participation of couples of reproductive age in the Family Planning Program in East Sumalata District, North Gorontalo Regency. The data used in this study consist of primary data collected through questionnaire surveys. The research population comprised 125 respondents, and a census method was employed. The analytical technique used to address the research problems and test the hypotheses was multiple regression analysis, conducted with the assistance of the Statistical Product and Service Solutions (SPSS) software for data processing. The findings of the study indicate that: (1) service delivery plays a positive and significant role in influencing the participation of couples of reproductive age; (2) promotion has a positive and significant effect on the participation of couples of reproductive age; (3) socialization activities have a positive and significant effect on the participation of couples of reproductive age; and (4) cultural factors have a positive and significant effect on the participation of couples of reproductive age. Furthermore, simultaneously, service delivery, promotion, socialization, and cultural factors have a positive and significant influence on the participation of couples of reproductive age in the Family Planning Program.